Cipp-Based Evaluation On English For Sport Science at Sport Education Study Program Of The University Of Ma’Arif Nahdlatul Ulama (Umnu) Kebumen - Hastri Firharmawan (Universitas PGRI Semarang, 2015)
The objective of this research is to evaluate the effectiveness of a program called English for Sport Science at Sport Education Study Program of Universitas Ma’arif Nahdlatul Ulama Kebumen (UMNU) based on CIPP. The study focuses on the elements of the CIPP by Stufflebeam (1971), namely: context, input, process, and product. It is an evaluation research and conducted qualitatively. The research was excecuted in 2016 at Sport Education Study Program of UMNU Kebumen, Central Java. The participants are the students, the English teacher, and chief of the program. Data were gained by in depth interview with the research participants, analysis of the existing documents, and observation. The data are analyzed through four steps by using interactive model as proposed by Miles and Huberman, (1994), as follow: 1) Data collection, 2) Data reduction, 3) Data serving; and, 4) Verification. The technique to use in data validation is by using source triangulation. The study found that the program was ineffective. There were four main factors to cause the ineffectiveness: First, the teaching context was less supportive to good teaching practices. Second, the inputs for the program were in lack of quality, indicated by unprofessional teachers. Third, the process of teaching and learning didn’t meet the stakeholders’ expectation; and last, the product indicated the students’ less competency on good communication skills required. In other words, the program didn’t achieve its goal; and, it is a clear prove to Dunkin’s and Biddle’s theory (1974) that context variables, presage variables or the input teachers, process variables, and product variables interrelatedly affect the success of teaching for a course program.